Analisis Variabelitas Volume Penjualan Premium, Minyak Tanah dan Solar pada PT. Masokan Multi Raya (Agen Premium dan Minyak Solar) di Kabupaten Waropen - Korinus Reri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine: 1) The development pattern of marketing volume of diesel, premium and kerosene at PT. Masokan Multi Raya as a premium and diesel oil agent in Waropen Regency during the period 2013-2021; 2) The level of significance of the variability of the marketing volume of diesel, premium and kerosene at PT. Masokan Multi Raya; 3) The average stability level related to the marketing volume of diesel, premium and kerosene at PT. Masokan Multi Raya. This type of research is comparative research. Data collection techniques are carried out using two approaches, namely through field research and library research. Data analysis techniques use quantitative analysis, namely development trend analysis, variability analysis, and relative variation analysis. The results of the study show that: 1) The development pattern of the marketing volume of diesel, premium and kerosene at PT. Masokan Multi Raya as a premium and diesel oil agent in Waropen Regency during the period 2013-2021 always increases; 2) There is a significant difference in the average sales volume of the three types of fuel oil products marketed by PT. Masokan Multi Raya as a premium and diesel oil agent (APMS) in Waropen Bawah District; and 3) Premium (VR = 0.0601) is a leading product of PT. Masokan Multi Raya in Waropen Bawah District with the most stable distribution of sales volume, while diesel (VR = 0.0864) has the most unstable sales volume and the lowest volume of kerosene.